RETHINKING OF INTELLECTUAL INTERVENTION ON THE SUBALTERN VOICE - Dian Windriani; Dyanti Mahrunnisya (English Department, STKIP PGRI Bandar Lampung, 2021)
Postcolonial theory on subaltern is presented in order to examine the subaltern’s voice in which its status is still debatable, whether they can voice for themselves or not. According to Spivak, subaltern does not have their own voice. She then proposes the idea of letting the intellectual intervention in voicing subaltern’s voice. However, her proposal is opposed by some theorist; one of them is Homi Baba. He believes that there is no need to borrow intellectual voice because the subaltern voicing themselves, due to the ambivalence of the colonizer’s power. This paper will examine how the debate related to the intellectual intervention in voicing the subaltern voice by contextualizing in the case of Sati and Bhuvaneswari.